2016
DOI: 10.1371/journal.pone.0155599
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Enteric Gram Negative Facultative Anaerobe Bacilli in Aerobic versus Anaerobic Conditions

Abstract: Antimicrobial treatments result in the host’s enteric bacteria being exposed to the antimicrobials. Pharmacodynamic models can describe how this exposure affects the enteric bacteria and their antimicrobial resistance. The models utilize measurements of bacterial antimicrobial susceptibility traditionally obtained in vitro in aerobic conditions. However, in vivo enteric bacteria are exposed to antimicrobials in anaerobic conditions of the lower intestine. Some of enteric bacteria of food animals are potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…We also found that TMP was more toxic in the absence than the presence of oxygen. This is in accordance with observations that the sensitivity of E. coli and Salmonella enterica to many antibiotics, including sulfamethoxazole/trimethoprim, was higher under anaerobic than under aerobic conditions ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that TMP was more toxic in the absence than the presence of oxygen. This is in accordance with observations that the sensitivity of E. coli and Salmonella enterica to many antibiotics, including sulfamethoxazole/trimethoprim, was higher under anaerobic than under aerobic conditions ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…Escherichia coli ATCC 25,922 was used as the quality control strain. The procedure was carried out in accordance with previous studies [ 60 , 61 ]. Several colonies (1–5) from the APEC strains, grown overnight on MacConkey agar (35 ± 2 °C), were added to a glass tube containing 3 mL sterile phosphate buffered saline (PBS) and vortexed in order to achieve a 0.5 McFarland inoculum (1.5 × 10 8 colony forming units (cfu)/mL; ATB 1550 densitometer, Biomerieux, Schaarbeek, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…MIC is routinely measured under aerobic laboratory conditions but the lumen of the large intestine is anaerobic. This change in environment has been shown to affect the MIC of E. coli (DeMars et al, 2016 ) so we applied an anaerobic penalty to the standard aerobic MIC to reflect this difference.…”
Section: Methodsmentioning
confidence: 99%
“…The upper limit of resistant MIC considered was 128 μg/mL. The anaerobic MIC penalty was assumed to range between the 1st percentile (−1.3) and 99th percentile (0) reported difference between anaerobic and aerobic tetracycline MIC for generic E. coli (DeMars et al, 2016 ). Therefore the lower-bound of the aerobic MIC distributions was decreased by 1.3, except for the susceptible MIC which could not be less than 0.…”
Section: Methodsmentioning
confidence: 99%